2020
DOI: 10.1021/acs.est.0c01343
|View full text |Cite
|
Sign up to set email alerts
|

Electron Flow Shifts from Anode Respiration to Nitrate Reduction During Electroactive Biofilm Thickening

Abstract: As electrons generated through substrate oxidation compete with electrodes, dissimilatory nitrate reduction to ammonium (DNRA), denitrification in bioelectrochemical systems in the presence of nitrate, and nitrate reduction through an electroactive biofilm (EAB) are unpredictable. We find that pathways of nitrate reduction are related to EAB thickness and that 76 ± 2 μm is the critical thickness of a biofilm at which both the inner and outer layers simultaneously include DNRA, leading to a maximum level of DNR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…This includes positive as well as negative effects and is in accordance with results from Zhou et al. [ 31 ] and Sun et al. [ 32 ] who observed limitations of the current density only after numerous batch cycles when thick biofilms had developed.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This includes positive as well as negative effects and is in accordance with results from Zhou et al. [ 31 ] and Sun et al. [ 32 ] who observed limitations of the current density only after numerous batch cycles when thick biofilms had developed.…”
Section: Resultssupporting
confidence: 92%
“…The results indicate that CDWD is not a decisive factor influencing the concentration response behavior for mixed-culture biofilms with CDWD up to 1.1 mg cm −2 as obtained after one to two weeks of cultivation time. This includes positive as well as negative effects and is in accordance with results from Zhou et al [31] and Sun et al [32] who observed limitations of the current density only after numerous batch cycles when thick biofilms had developed. Such limitations can result from concentration gradients that develop in the biofilms [4].…”
Section: Mechanisms Of the Biofilm Adaptationsupporting
confidence: 92%
“…Another virtue of using NO 3 − feedstock lies in its rich distribution in wastewater. The abundant nitrate in wastewater offers sufficient reactants for NO 3 − reduction reaction (NO 3 − RR) routes [17][18][19][20] . Instead of the partial reduction of NO 3 − to N 2 for its purification, the eight-electron transfer reaction for NO 3 − to NH 4 + synthesis provides an opportunity for the valueadded conversion of contaminative NO 3 − into ammonia as an economically competitive product.…”
mentioning
confidence: 99%
“…Cells on the anodes in the MFC setups were stained with a LIVE/DEAD BacLight bacterial viability kit, showing green or red depending on the cell membrane permeability of live and dead cells (Zhou et al, 2020). We then performed CLSM on the MFCs carbon cloth electrodes of the engineered strains and DL0 strain.…”
Section: Resultsmentioning
confidence: 99%